Solar Power Installation Simulation in SDN Rancagong 1 and 4 Using PVSyst to Support the Physical Standard of Comfort - Nicholas Pranata; Niki Prastomo; Vincentius Rayza Lee; Ricardo Linelson (Jurnal Surya Energy, 2025)
Physical comfort in the learning environment relies on the use of good electrical equipment, which significantly supports the learning process. To enhance comfort, it is essential to maximize the use of electrical appliances, although this can lead to increased energy consumption. Most of the primary energy for power generation comes from non-renewable sources, which contribute to pollution. In Indonesia, not all regions have access to electricity that meets desired comfort standards. One such area is SDN Rancagong 1 and 4, where the use of power tools to support the learning process is still minimal. Measurements of comfort standards revealed that the air temperature exceeded the SNI 03-6572-2001 standard by 4°C, while humidity levels surpassed the same standard by 9%. Additionally, illumination levels were less than a third of the SNI 6072-2020 lighting standard. Qualitative feedback from room occupants supports these findings. To address these issues, the proposal includes the use of renewable energy sources such as solar energy. To avoid losses and ensure effective implementation, simulations were conducted using PVSyst software. The results indicated a power generation potential of 7,829.33 kWh per year, with a performance ratio of 49%, a solar fraction of 100%, an SOW cycle of 98.4%, and a static SOW of 90%. With this power output, it is anticipated that electricity can be provided for equipment that enhances comfort standards, such as air conditioning and additional lighting.